Cognitive Behavioral Therapy Alleviate Postpartum Depression Symptomps - Lathifah Tiya Paramudita; Rahmi Nurrasyidah; Sugita Sugita; Dwi Retna Prihati (Yayasan Inspirasi El Burhani, 2023)
Introduction: Postpartum women are prone to experience psychological disorders such as baby blues and postpartum depression. Postpartum depression can occur due to prolonged baby blues. Complaints that are often felt include anxiety, difficulty sleeping, lack of confidence and changes in mood. These symptoms can develop into more severe symptoms not only of not being able to pay attention to the baby but also of women being prone to suicide. various interventions have been developed including pharmacological interventions. Women who have been intervened with drugs complain of the many side effects they experience. Non-pharmacological treatments such as cognitive behaviour therapy have the potential effect to relieve symptoms of depression. Cognitive Behavior Therapy is a psychological intervention model that trains the perceptions of postpartum women to apply solution-based thinking. This technique is often used to intervene in psychological problems. Aims: The review is to summarize the effectiveness of cognitive behavioural therapy in reducing postpartum depression Methods: This research is a literature study based on 7 articles screened based on PICO, inclusion and exclusion criteria. We did a review based on research with RCT methods and pre-experimental studies. Review use database Pubmed, Science Direct, and Google Scholar Results: Based on the available evidence, Both CBT offline and online can reduce symptoms of postpartum depression. A trained midwife can perform CBT. The CBT mobile application can also be developed as a virtual therapy for women with postpartum depression. CBT can be applied during the antenatal period or during the postpartum period. Conclusion: CBT offline, online or application effective to treat postpartum depression